Incidence of Philanthrocapitalism in Education — bibliometric study based on the CAPES theses and dissertations database and scientific articles on the Scielo portal - Soares Beserra Capoano, Adriana; DE FREITAS ADRIÃO, THERESA MARIA (Educação, Escola & Sociedade, 2022)
This paper is the result of a bibliometric survey on the performance of philanthrocapitalism in Brazilian basic education, stages - elementary and secondary - based on academic production - Theses and Dissertations (Academic Masters) - from the Bank of Theses and Dissertations of the Coordination for the Improvement of Personnel of Higher Level, and scientific articles in the Portal Scientific Electronic Library Online (Scielo). The survey, on both bases, was obtained by the descriptors “philanthrocapitalism”, “venture philanthropy”, “new philanthropy” , “philanthropy”, "philanthropy" "philanthropist" and "philanthropic”. The analysis of the abstracts was based on Adrião, 2015; Adrião and Domitiano, 2018; Robertson and Verger, 2012; Ball and Olmedo, 2013. The main result is that no specific research was located on philanthrocapitalism in education in BRAZIL, based on the criteria of this survey, however there is evidence of its role in public education. Keywords: Privatization. Philanthrocapitalism. “Venture Philanthropy”. Philanthropy. Philanthropic.